Outcomes of corticosteroid injection and percutaneous release in treatment of trigger finger at tertiary hospital of Eastern Nepal. - Gupta, Mithilesh Kumar; Chaudhary, Ajay; Mahato, Ajay (Birat Journal of Health Sciences, 2021)
Introduction: Trigger finger or stenosing tenosynovitis is a common cause of painful fingers and thumb that result in painful triggering, snapping or locking of fingers on flexion and extension of involved digit. Available treatment options for this condition are NSAID, splints, intralesional steroid injection, percutaneous release and open release of tendon sheath. Objectives: To study the clinical and functional outcomes and complications of corticosteroid injection and percutaneous release in management of trigger finger. Methodology: In this prospective study, sixty patients who presented with Grade 2 to Grade 3 trigger finger were placed into two groups. Group A(30 patients) were treated with intralesional steroid (40 mg of methylprednisolone) injection. Group B (30 patients) underwent percutaneous surgical release of affected tendon sheath. Both group of patients were treated in outpatient department. Patients of both groups were then asked to follow on scheduled time interval of two-week, six-week, three-months and six-months of period and their progress were recorded. Results: The baseline VAS score before intervention in group A (5.82) and group B (6.12) was statistically significant. In group B there was significant improvement of VAS score till 6 months of follow up. However, in group A there was significant improvement of VAS score by 3 months of follow-up, but by end of 6 months it again raised to 2.14. Yet it was far better than baseline VAS score. Conclusion: In our study both corticosteroid injection and percutaneous trigger finger release were found to be much effective in management of trigger finger.